Current Situation in Teaching Physical Education at Universities in the Slovak Republic - Alena Buková; Klaudia Zuskova; Agata Horbacz; Erika Chovanová; Natalia Bielikova; Svitlana Indyka (Фізичне виховання, спорт і культура здоров’я у сучасному суспільстві, 2020)
The aim of the study was to draw an accurate picture of the current situation in teaching physical education at universities in the Slovak Republic. The authors seek further ways of sustaining and developing it as a prerequisite for a healthy lifestyle of the university population. The analysis confirmed that technical universities in Slovakia show a substantially more positive approach towards physical education in their curriculum than social and natural sciences universities. Of the 105 monitored faculties of public universities, physical education is listed as a compulsory subject at 13 out of 27 faculties of technical universities and only at 9 out of 78 faculties with a humanities focus. Physical edu- cation is present at every faculty of technical universities in our research; the situation is much less favorable at all other universities, where as many as 45 faculties do not offer physical education in their curriculum. Among them are faculties that educate future primary and secondary school teachers. We further found that directly affiliated university departments of Physical Education have a better chance of maintaining sport and physical activity at university, whether as compulsory part of the higher education curricula or as extracurricular optional sporting activities.